The Strategic Value of Africa as the New Market and Korea’s Economic Cooperation with Africa - Y. Park (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
Africa is rising as the new market in the 21st century. Before the 2000s Africa was regarded as a “continent of crisis” plastered with poverty and war. However, it is now being spotlighted as the ‘last new market on Earth’ due to its development potential. Its value is being reevaluated because it presents new opportunities as an unexplored market. It present opportunities across a wide range of industries: from consumer goods to manufacturing, agriculture, natural resource development and infrastructure. Korea has been ignorant of Africa’s development potential till the mid-2000s but is now looking at Africa as a new opportunity market or cooperation partner. It is taking diverse measures such as through state visits and increase of development aid to strengthen cooperation. Korea perceives Africa’s potential from a future oriented perspective and is expanding economic cooperation from a long-term standpoint. Consequently, Korea is working towards establishing a future oriented partnership with Africa based on mutual trust by identifying core partnership projects that meet the needs of Africa. Korea seeks substantiality of its economic partnership with Africa by identifying priority countries of cooperation.